2005
DOI: 10.1101/gad.1304805
|View full text |Cite
|
Sign up to set email alerts
|

Polarity of the mouse embryo is established at blastocyst and is not prepatterned

Abstract: Polarity formation in mammalian preimplantation embryos has long been a subject of controversy. Mammalian embryos are highly regulative, which has led to the conclusion that polarity specification does not exist until the blastocyst stage; however, some recent reports have now suggested polarity predetermination in the egg. Our recent time-lapse recordings have demonstrated that the first cleavage plane is not predetermined in the mouse egg. Here we show that, in contrast to previous claims, two-cell blastomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
179
4
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(196 citation statements)
references
References 36 publications
12
179
4
1
Order By: Relevance
“…The results published by Roberts group are in direct conflict with the data recently published by Motosugi and colleagues [6] who used timelapse video microscopy and fluorescent cell labeling to demonstrate a lack of patterning in preblastocyst mouse embryos. Multiple conflicting reports have been published on this subject [2][3][4][5][6].…”
Section: Significance and Future Perspectivescontrasting
confidence: 56%
See 2 more Smart Citations
“…The results published by Roberts group are in direct conflict with the data recently published by Motosugi and colleagues [6] who used timelapse video microscopy and fluorescent cell labeling to demonstrate a lack of patterning in preblastocyst mouse embryos. Multiple conflicting reports have been published on this subject [2][3][4][5][6].…”
Section: Significance and Future Perspectivescontrasting
confidence: 56%
“…Multiple conflicting reports have been published on this subject [2][3][4][5][6]. While it is not clear at this stage what accounts for the differences in the results obtained by various groups, one possible explanation is variation in the mouse strains used to obtain embryos.…”
Section: Significance and Future Perspectivesmentioning
confidence: 87%
See 1 more Smart Citation
“…The earlier-dividing two-cell blastomere did not give rise to any trophectoderm. However, this proposal contradicts all previously published observations regarding developmental potential and fate of cells from the two-cell embryo, because all other groups have reported contribution of both two-cell blastomeres to both ICM and TE (Gardner, 2001;Piotrowska et al, 2001;Marikawa, 2003, 2005;Chroscicka et al, 2004;Hiiragi and Solter, 2004;Plusa et al, 2005a;Motosugi et al, 2005;PiotrowskaNitsche and Zernicka-Goetz, 2005). Before these observations can be considered as changing the paradigms of early mouse development, it is essential to explore whether this lineage relationship holds true in other mouse strains and if it can be reproduced by other groups using alternate lineage tracing methods.…”
Section: Polarity In the Oocyte And Blastocystmentioning
confidence: 66%
“…Unlike fertilized oocytes, no tendency for the first two parthenogenetic blastomeres to follow different fates was found, supporting the conclusion that the fertilization process contributes to setup of embryonic patterning. In contrast with the above claims, recent time-lapse recordings have shown that the first cleavage plane is not predetermined but is defined only by the topology of the two apposing pronuclei in the mouse embryo [9] and that the polarity of the mouse embryo is established at the blastocyst stage and is not prepatterned [18,19]. Controversy still exists as to whether the individual blastomeres from twocell-stage embryos have identical developmental fates.…”
mentioning
confidence: 80%